‘One should marry in church for a strong marriage’: Why people in Soviet Russia in the 1920s kept getting married in church - M. A. Grafova (Шаги, 2024)
This article explores religious marriage in the USSR during the New Economic Policy (NEP). From the start, the Soviet authorities made great efforts to gradually eliminate religious beliefs within Soviet society. One of the first steps in that direction was the removal of marriage from Church jurisdiction. Moreover, Soviet power was constantly trying to compromise the tradition of religious marriage. However, many people still preferred to be married in church in addition to civil registration. A wide range of historical sources studied in this research (political and sanitary propaganda, communist and entertainment media, printed court reports) reveals that the new “civil” marriage was considered to be extremely unreliable by “ordinary” people, especially young girls of marriageable age and their parents. It was too easy to enter into such a marriage and to end it. It was associated with divorces, alimony suits, almost legalized cheating. The intention to marry in church at least meant a serious commitment, a willingness to take responsibility. Also, even many years later, during the Census of 1937, the majority of the population of the USSR considered themselves believers. This situation continued until a crucial change in ideology and social politics took place in the late 1920s, when most churches were closed. This study is focused on psychology of the “little man” in an epoch of global political and social changes.